ENGLISH FOR ACADEMIC PURPOS (EAP): A BRIDGE TO SUCCESSFUL STUDY IN A FOREIGN UNIVERSITY - Muslih Hambali (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2011)
This paper aims at discussing the role of EAP in preparing students planning to study oversea based on Indonesia context. The success of one’s study in a foreign university where English is as medium of instructions can be determined by how well his capability to use both spoken and written English. We might often find a students, though, in fact, smart in his discipline, get unsatisfactory result, or even fail in completing his studies because of English. Normally if one has good English performance during EAP program, he might have no trouble  facing his future studies in English. Previous experience of conducting EAP program has proved how the program could contribute to the overseas studies of the EAP participants. Therefore, EAP program needs to be well prepared for the needs of academic purposes. The major concerns to address to the students is the study of English skills. Since the EAP program should begin with General English (GE) and then Academic English, the language level of learners, course length, target, and materials should be considered. If the average of baseline TOEFL score of students is above 450 as a reference for example, the number of hours for AE should be much bigger.